Missed at first Glanz: Glanzmann thrombasthenia initially misdiagnosed as Von Willebrand Disease. (February 2019) - Doherty, Dearbhla; Singleton, Evelyn; Byrne, Mary; Ryan, Kevin; O'Connell, Niamh M.; O'Donnell, James S.; Lavin, Michelle
Abstract: Glanzmann thrombasthenia (GT) is an autosomal recessive bleeding disorder caused by a defect in platelet integrin αIIbβ3. Given the rarity of the condition (1/1, 000, 000), assessment and diagnosis should be undertaken in a specialist centre. We report the case of a 34 year old woman with severe menorrhagia and a childhood diagnosis from another centre of Von Willebrand Disease. She had an extensive bleeding history, with epistaxis, menorrhagia and postoperative bleeding requiring multiple previous transfusions. Repeat haemostatic workup in our centre revealed normal Von Willebrand levels but abnormal platelet aggregation consistent with Glanzmann thrombasthenia. Antibody screening detected both anti-HLA and anti-αIIbβ3 antibodies, complicating subsequent haemostatic management. This case highlights the importance of diagnostic accuracy, the potential negative sequelae of misdiagnosis and subsequent therapeutic interventions.